Standarization of a Protocol of Immunohistochemistry for the Detection of Brain Microglia in Wistar Rats - Ramírez Chan DDS, MSc, PhD, Karol; Jaime Fornaguera-Trías PhD, Jaime (Odovtos - International Journal of Dental Sciences, 2017)
Objective: Standardize a protocol of immunohistochemistry that has been widely used in C57BL/6J mice to identify microglia of the central nervous system in Wistar rats. Materials and Methods: This research activity was carried out in two parts. In the first part, a protocol of immunohistochemistry was implemented to identify microglia in the central nervous system of 6 Wistar rats. A primary antibody with reactivity to rat and a specific secondary antibody to the primary were used. Once the protocol was established in rats’ brains, an immunological challenge was produced with the intraperitoneal application of lipopolysaccharide in 2 Wistar rats, in order to evidence the changes in microglia morphology. Results and Discussion: We demonstrate that without making major modifications to the original protocol, it can also be used to identify microglia in adult Wistar rats. In the near future, this immunostaining protocol will be applied to elucidate the bidirectional interaction between the brain and the immune system, under homeostatic conditions and different physiological and pathological stimuli.